PERAN GEODESI DAN GEOMATIKA DALAM IMPLEMENTASI SUSTAINABLE DEVELOPMENTGOALS NOMOR 14 DI INDONESIA - Eka Djunarsjah; Hafidz Akbar Fakhrurozi (Universitas Pendidikan Indonesia (UPI), 2021)
The 14th Sustainable Development Goals has less in common with the others, which mostly concern about poverty, hunger, inequality, healthy and education. The difference is that the goal doesn’t really linkages, and it is more likely independent. Apart from that, the goal is mainly talk about how marine resources can be used sustainably without being harmful to environment itself. Therefore, the academic sector should be taken into account in order to accomplish the goal through its science capacity and analytic. Geodesy and Geomatics Science will be a very useful tools in creating sustainable use of oceans and furthermore will help to assist government in decision making. The topic of Remote Sensing and Geographic Information System will be the main discussion in order to help the implementation of 14th SDGs which will be explained in technical aspects section. This paper come up with recommendation for government and its policy through the discussion in the legal and institutional aspects.Keywords: 14th SDGs, Decision making, Geodesy and geomatics, Sustainable Development, Marine resources;